Orbital Pseudotumor: Neurosurgical Perspective - Pedro Henrique Karpinski; Giovana S. Ceconello; Leonardo C. Welling (Brazilian Neurosurgery)
Idiopathic orbital inflammation is the third most common orbital affection, characterized by a benign inflammatory process, which is neither infectious nor neoplastic and can affect any orbital tissue. A 31-year-old female patient was referred to neurosurgical evaluation due to left orbital pseudotumor, which was nonresponsive to high doses of corticosteroid therapy. During the neurological examination, we identified reduced visual acuity, complete external ophthalmoplegia, ocular pain, and severe proptosis. A neurosurgical intervention with lateral orbitotomy was performed, with great pain relief. In the present case report, we discuss the disease and its natural course and call the attention of neurosurgeons to prompt intervention in selected cases.